Endoscopic cartilage myringoplasty with the removal of a small rim of the external auditory canal to repair marginal perforations - Zheng-cai Lou (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Objective To evaluate the graft success rate and postoperative hearing gain for marginal perforations using endoscopic cartilage myringoplasty with the removal of a small rim of the external auditory canal (EAC). Study design Prospective case series. Materials and methods We performed a prospective study in 41 patients with marginal perforations who underwent endoscopic cartilage myringoplasty with the removal of a small rim of EAC. Patients were followed up for 6 months. Results Of the 41 patients with unilateral marginal perforation included in this study, the graft success rate was 100% (41/41). The mean ABG improved from 11.31 ± 9.71 dB preoperatively to 7.31 ± 2.32 dB postoperatively for small-and medium-sized perforations (P = 0.13); the mean ABG improved from 21.46 ± 8.39 dB preoperatively to 9.84 ± 2.41 dB postoperatively for large perforations (P < 0.05); the mean ABG improved from 28.79 ± 6.74 dB preoperatively to 10.13 ± 3.56 dB postoperatively for subtotal and total perforations (P < 0.05). There were no cases of graft lateralization or significant blunting or atelectasis or graft adhesions. Three patients developed postoperative otorrhoea and five patients had mild myringitis. Conclusions Endoscopic cartilage myringoplasty with the removal of a small rim of the EAC is simple and feasible, showing a high graft success rate and minimal complications for repairing marginal perforations.